2020
DOI: 10.1016/j.acra.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Interventional Radiology Training Programs: What You Need to Know

Abstract: The COVID-19 pandemic has affected medical education in unprecedented ways. Herein, we briefly describe the affects of COVID-19 on Interventional Radiology residency training and summarize up to date guidance by governing bodies and key stakeholders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 1 publication
3
46
0
5
Order By: Relevance
“…COVID-19 dramatically impacted patient care [ 6 ] and had far-reaching effects on training in surgical programs [ [7] , [8] , [9] , [10] ]. Prior studies showed that COVID-19 epidemic is associated with significant reduction in residents training and reduction in medical education in different specialties [ 7 , 8 ]. The impairment may be more severe in surgical specialties, where hands-on training cannot be replaced by distance education [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 dramatically impacted patient care [ 6 ] and had far-reaching effects on training in surgical programs [ [7] , [8] , [9] , [10] ]. Prior studies showed that COVID-19 epidemic is associated with significant reduction in residents training and reduction in medical education in different specialties [ 7 , 8 ]. The impairment may be more severe in surgical specialties, where hands-on training cannot be replaced by distance education [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing and isolation are important stressors that are perceived as having a negative impact [44]. The disruption of training programs, reduced practical workload in a residents specialty, slowdown of research careers and redeployment are further stressors that may bring burnout, fatigue and loss of morale [45][46][47]. Residents also were concerned that the pandemic would adversely affect their completion of training and nearly half the respondents had an anxious feeling about their training future [48].…”
Section: Uncertainties and Mental Healthmentioning
confidence: 99%
“…immunosuppression). Deployment should consider such information accordingly [46]. Additionally, a sufficient Covid-19 testing capacity for staff, PPE and feasible shift schedules are seen as viable to reduce exposure and prevent burnout [50].…”
Section: Uncertainties and Mental Healthmentioning
confidence: 99%
“…For IR programs, the ACGME has relaxed some of their requirements in an effort to deal with the decreased procedure volumes and decreased in-person time on clinical rotations. 2 For example, IR residents can still complete their postgraduate year (PGY-5) year with less than 500 cases provided they meet the 1000 required cases by the end of their second independent IR residency year. Similar flexibility exists for IR residents unable to complete the mandated intensive care unit rotation before the PGY-5 year.…”
mentioning
confidence: 99%
“…Similar flexibility exists for IR residents unable to complete the mandated intensive care unit rotation before the PGY-5 year. 2 Radiologists in the United States and throughout the world should be proud how our professional community has stepped up to the challenges presented by the COVID pandemic to continue to train the residents and fellows who represent the next generation of diagnostic and interventional radiologists.…”
mentioning
confidence: 99%